Description of the larva of Ochthebius capicola (Coleoptera: Hydraenidae) from marine rockpools of South Africa - Sabatelli, Simone; Audisio, Paolo; Trizzino, Marco; Giulio, Andrea Di (Zootaxa, 2013)
Larval instars II and III of Ochthebius (Ochthebius) capicola (Péringuey 1892) from South Africa are described and illus-trated by SEM, including a detailed analysis of their chaetotaxy and porotaxy. Specimens used in this study were collected with adults of the same species in marine rockpools. The larval morphology of O. capicola is compared to that of other members of the same genus occurring in this habitat, contributing to the current taxonomic and phylogenetic debate on the intrageneric taxonomy of Ochthebiinae.